2022
DOI: 10.3389/fnut.2022.889303
|View full text |Cite
|
Sign up to set email alerts
|

Fried food consumption and the risk of pancreatic cancer: A large prospective multicenter study

Abstract: Background and aimsWhether fried food consumption is associated with the risk of pancreatic cancer remains elusive. We aimed to examine this association in a US population.MethodsA population-based cohort of 101,729 US adults was identified. Fried food consumption was assessed with a validated food frequency questionnaire. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated. Explanatory analyses were conducted to identify main contributor(s) to the observed association.ResultsDuring an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Park et al (2000) have shown that consuming French fries reduces gastric cancer. Previous association studies of pancreatic cancer and fried potatoes also suggested that the antioxidant properties of potatoes may have resulted in reducing the risk of pancreatic cancer [9]. Lee et al (1995) have also reported a reduction in gastric cancer with the consumption of fried meat.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Park et al (2000) have shown that consuming French fries reduces gastric cancer. Previous association studies of pancreatic cancer and fried potatoes also suggested that the antioxidant properties of potatoes may have resulted in reducing the risk of pancreatic cancer [9]. Lee et al (1995) have also reported a reduction in gastric cancer with the consumption of fried meat.…”
Section: Discussionmentioning
confidence: 96%
“…Although most studies found a significant increase in cancer risk with a high intake of fried foods (meat, fish, eggs, and potatoes), some studies found that the intake of heterocyclic amines within the usual dietary range from the frying process was unlikely to increase the incidence of cancer in the colon, rectum, bladder, or kidney [37]. In addition, it has been reported that the consumption of French fries was inversely proportional to the risk of pancreatic cancer [9]. Additionally, dietary acrylamide intake has not been associated with the risk of gastrointestinal cancer [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased PC risk has been associated with higher exposure of these diets; however, evidence of temporal relationship and pathogenesis remains unclear. More recently, contradictory findings of deep-fried foods inversely related to risk of PDAC was found in prospective study (Figure 1) [83].…”
Section: Food Carcinogensmentioning
confidence: 97%
“…The consumption of deep-fried foods has not been specifically studied in relation to cancer; however, there have been reports of heightened risks of certain types of cancers being correlated with the intake of deep-fried foods. Consumption of food that has undergone deepfrying has also been associated with an elevated risk of developing pancreatic cancers 40,41 . The intake of fried foods in general has been associated with the onset of oral and pharyngeal cancers, as well as esophageal malignancies and laryngeal conditions.…”
Section: Deep-fried Foodsmentioning
confidence: 99%